Sentencing Risk: Temporality and Precaution in Terrorism Trials1. Issue 3 (12th September 2013) - de Goede, Marieke; de Graaf, Beatrice
Abstract : In debates on the preemptive measures of the war on terror, criminal law is often regarded as the antithesis to exception—a conventional mode of response that acts on the basis of past harm. Since September 11, 2001, however, significant new terrorism laws have been adopted in most countries in order to make possible the disruption and prosecution of potential terrorists engaged in preparatory activities. Thus, ancillary acts undertaken increasingly in advance of actual violence are brought within the remit of criminal law. This paper engages the question of the precautionary turn in criminal law itself, and how it plays out in actual courtrooms. We examine the terrorist trial as a performative space where potential future terror is imagined, invoked, contested, and made real. By focusing on the cases of the Hofstad group in the Netherlands, and the Rhyme trials in the UK, the paper examines how present criminal offenses involving terrorist aims and intent are constituted through the appeal to potential future violence. In conclusion, the paper teases out the political dynamic of secondary risk management that—frequently—underlies contemporary terrorism prosecutions.